Hematoma size as major modulator of the cellular immune system after experimental intracerebral hemorrhage - Illanes, Sergio; Liesz, Arthur; Sun, Li; Dalpke, Alexander; Zorn, Markus; Veltkamp, Roland (Neuroscience letters, 2011)
Inflammatory cascades are increasingly recognized as an important pathophysiological mechanism in intracerebral hemorrhage (ICH). In contrast, the effect of ICH on the systemic immune system has barely been investigated. We examined the effects of different hematoma volumes on immune cell subpopulations in experimental murine ICH. In C57BL/6 mice, ICH was induced by striatal injection of autologous blood (10, 30 or 50μL). Control animals received the respective sham operation. Three days after ICH induction, differential blood leukocyte counting was performed. Lymphocyte subpopulations were further characterized by flow cytometry in blood, spleen, lymph node and thymus. Infectious complications were studied using microbiological cultures of blood and lungs. Only after large ICH a marked decrease of leukocyte counts and most lymphocyte subsets was observed in all organs. Despite this general leukocytopenia, a significant, up to 10-fold increase, was detected in the monocyte population after extensive hemorrhage. After moderate ICH induction, only specific lymphocyte subpopulations were differentially affected. Mature thymic cells were unaffected while immature CD4+CD8+ cells were depleted by over 90% after large ICH. A significant proportion of mice with extensive ICH (36.4%) developed spontaneous pneumonia and/or bacteremia while none of the sham operated mice had infectious complications. The ICH size determines the extent of systemic immunomodulation. Large ICH predisposes animals to infections.
Available online 3 December 2010
Gesehen am 01.07.2022